Investigation of recast layer of non-conductive ceramic due to micro-EDM - Mohamed, Abd. Rahman; Asfana, Banu; Ali, Mohammad Yeakub (Trans Tech Publications, Switzerland, 2014)
This paper presents the investigation of minimum recast layer of zirconium oxide (ZrO2) due to micro-EDM using EDM-3 synthetic oil as dielectric fluid and tungsten as the tool electrode with control parameters of rotational speed and gap voltage. The investigation was performed using multi-process micro machine tools DT 110. The recast layer thickness was observed using scanning electron microscope and its hardness was measured using micro-Vickers hardness tester. The hardness data were analyzed and an empirical model was developed. The optimum value for minimum recast layer hardness was 873.46 Hv with rotational speed of 395 rpm and gap voltage of 110 V.